Assessment of Groundwater Quality in the Western Part of Bayero University New Campus and it’s Environs - Auwal, M. A; Kwaya, M. Y (Covenant Journal of Physical and Life Sciences, 2022)
This research aimed at assessing the quality of groundwater for safe drinking in the western part of BUK’s new campus and its environs, Kano state. In achieving the aim, a total of ten (10); five (5) boreholes and five (5) hand-dugged wells were selected at random across the area, taking into consideration the fact that thousands of staff and students depend on these sources. Water from each of the selected wells was sampled in a sterilized 500 mL plastic container and taken to the laboratory for analysis. Fourteen relevant parameters on the test of water quality were taken into consideration. Analysis of physical parameters was made in-situ using a PC400 portable pH/COND/EC/Temp meter. The result reveals that electrical conductivity is the only parameter with a mean concentration of 437.9 mg/L higher than the maximum permissible limit of 400 mg/L sets by the World Health Organization, 2011. The mean values of other physical parameters are within the standards. Chemical parameters analysis reveals that chloride (335.5 mg/L), calcium (781.3 mg/L), sodium (62.5 mg/L) and magnesium (115.9 mg/L) are the parameters with concentrations higher than the maximum permissible levels of 250 mg/L, 100 mg/l, 50 mg/L, and 50mg/L respectively, all in Tudun Malumai area. Therefore, with the exception of this area, all other sources investigated are safe for drinking by meeting the standard requirements. The high concentration of chloride in the Tudun Malumai area is attributed to the use of inorganic fertilizers and animal feeding. Distillation, one of the oldest, and yet still very effective methods of purifying water sources is highly recommended.